PERLINDUNGAN HUKUM TERHADAP HAK PEKERJA PEREMPUAN MENJADI PEMIMPIN DI RITEL SEDANG: Legal Protection Of Women Worker’s Rights To Become Leaders In Medium Retail - Loardista Alfi; Wahyuni Retnowulandari (Faculty of Law, Trisakti University, 2024)
Inequality of rights results in female workers feeling unworthy of being leaders rather than men at work. Basically, women workers should receive their full rights without discrimination. Various regulations in Indonesia have guaranteed the rights of women workers, such as: The Convention on the Elimination of all Forms of Discrimination Against Women (CEDAW), the Universal Declaration of Human Rights (UDHR), Law No. 13 of 2003 on Labor, and the 1945 Constitution. This research aims to describe the legal protection of women workers' rights to become leaders in the workplace. This research uses a normative type with the nature of the research is descriptive then draws conclusions deductively. The results of the study state that in retail companies the applicable regulations are in accordance with CEDAW with the existence of legal protection and social security to female workers, although the company has not fully implemented legal protection to female workers because in recent years the head of the shop is still dominated by men.